Dendritic cells under the control of the preimplantation embryo secretome: an in vitro study - Christiana Kyvelidou; Sofia Haselrieder; Maria von Gierke; Johanna M. Gostner; Wolfgang Biasio; Barbara Wirleitner; Christine Heufler; Bettina Toth; Susanne Hofer-Tollinger (BMC, 2024)
Abstract Objective To study the crosstalk between maternal immune cells and the developing embryo by investigating the immunogenic properties of human blastocyst spent media (SM) on dendritic cells. Methods In this prospective multicenter experimental study, human preimplantation embryo spent media were collected after blastocyst formation, grouped based on successful or unsuccessful implantation, and analyzed by protein array or used to stimulate monocyte derived dendritic cells (moDC). The immunomodulatory properties of SM on moDC were investigated by analyzing changes in phenotype, cytokine secretion, indoleamine 2,3-dioxygenase (IDO) activity, and ability to activate T cells. Results A plethora of cytokines and growth factors secreted from preimplantation embryos was detected. Exposure to embryo SM altered the phenotype of moDC in a manner dependent on the implantation outcome. Specifically, SM from non-implanted embryos increased the expression of co-stimulatory molecules and activation markers on moDC. Furthermore, SM treated dendritic cells secreted low levels of cytokines and growth factors and were able to stimulate naïve T cells. Activation of IDO was decreased in moDC after stimulation with SM. Conclusions Our findings show that human preimplantation embryos secrete an abundance of molecules with the ability to significantly affect and even regulate immune cells in their environment.